Forage and grain yields of wheat and barley - K. Bolsen; L.L. Berger; W. Moore (Kansas Agricultural Experiment Station Research Reports, 1976)
Our objectives were to determine the effects of variety and stage of plant growth at harvest on forage and grain yields of wheat and barley. Plots were grown at the Animal Science and Industry Farm near Manhattan in 1973-74 and 1974-75 and at the South Central Kansas Experiment Field at Hutchinson in 1974-75. Hard red winter wheat varieties used were Parker, Eagle and Sage; soft red winter wheats were Arthur-71 and Blue Boy II. Three winter barley varieties were Paoli, Jefferson and Kanby. All cereals were harvested for forage in boot, milk and dough stages of plant growth and each treatment was replicated four times. A 60-sq.-ft. area was mower-clipped from each plot at each stage of growth to measure forage yields. Approximately 1 to 2 inches of stubble remained. A 12-sq.-ft. area was taken to determine grain yield.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Forage yields; Grain yields; Wheat; Barley